2011
DOI: 10.5402/2011/929251
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index Impacts In Vitro Fertilization Stimulation

Abstract: The objective of the study was to prospectively determine if body mass index (BMI) is predictive of live birth rates in patients undergoing IVF. The prospective study enrolled 117 infertility patients with the primary outcome measure being IVF success rates. Mean BMI did not differ between patients with successful outcomes and those without successful outcomes. There was a significant positive correlation between BMI and the number of stimulated follicles (r = 0.19, P < .05). A significant negative correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
1
11
0
1
Order By: Relevance
“…Many studies have reported a negative effect of obesity on fertility (Table 1). Obese women show a reduced response to gonadotrophin stimulation, resulting in lower estradiol levels and fewer collected follicles, with equal or reduced live birth rates being reported post transfer (Esinler et al 2008;Hill et al 2011;Marquard et al 2011). Follicular fluid bathing the cumulus-oocyte complex in obese women contains markedly increased levels of triglycerides and free fatty acids, potentially contributing to reduced oocyte quality (Robker et al 2009).…”
Section: Obesity and Periconceptional High-fat Dietsmentioning
confidence: 99%
“…Many studies have reported a negative effect of obesity on fertility (Table 1). Obese women show a reduced response to gonadotrophin stimulation, resulting in lower estradiol levels and fewer collected follicles, with equal or reduced live birth rates being reported post transfer (Esinler et al 2008;Hill et al 2011;Marquard et al 2011). Follicular fluid bathing the cumulus-oocyte complex in obese women contains markedly increased levels of triglycerides and free fatty acids, potentially contributing to reduced oocyte quality (Robker et al 2009).…”
Section: Obesity and Periconceptional High-fat Dietsmentioning
confidence: 99%
“…In the final analysis, 105 eligible studies (19 prospective and 86 retrospective cohort studies) were included, involving more than 271,632 pregnant women (Figure 1). 14,15,28–130 The main characteristics of included studies were summarized in Table S1. In total, 100 studies reported the association between maternal BMI and CPR among pregnant women undergoing ART, among which 53 reported MR and 51 reported LBR (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…In total, 100 studies reported the association between maternal prepregnancy body weight and CPR after ART 14,15,28–55,58–80,82–117,119–122,124–130 . At per‐woman level, 54 studies, involving 109,688 pregnant women, showed an inverted J‐shaped relationship between maternal BMI and CPR ( P n < 0.01) 14,28–31,34–36,40,41,44,46,47,49,53,58,60,61,64–68,75,76,78,82,85,86,88–95,97,99,103–106,109,112–114,119,121,124,126–128,130 . Compared with the reference BMI value (21.75 kg/m 2 ), BMI > 22.5 kg/m 2 was associated with lower CPR (Figure 2a and Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…В некоторых странах страховые компании не оплачивают протоколы ЭКО женщинам с ожирением [40]. Ряд авторов отмечает, что у женщин с ожирением в процессе стимуляции увеличивается доза гонадотропинов и число дней, необходимых для эффективной стимуляции [41][42][43]. Причем у женщин с ИМТ более 30 кг/м 2 доза гонадотропинов превышает дозу у женщин с нормальным весом и сниженным овариальным резервом.…”
unclassified